Recent development and research priorities on cool and super cool materials to mitigate urban heat island. (December 2020) - Santamouris, M.; Yun, Geun Young
Abstract: The urban heat island is increasing the temperature of cities up to 10 °C and has a very important impact on energy, environmental quality and health. Materials used in the building and urban fabric affect the urban thermal balance and contribute highly to urban overheating. The article presents the progress achieved on the design, development and implementation of mitigation materials presenting a low and very low surface temperature. The recent technological progress and developments concerning natural, light colour, IR reflective, PCM doped, thermochromic, fluorescent, photonic and plasmonic materials is presented. Experimental results on the cooling capacity and the thermal performance of conventional and advanced materials are described in a comparative way. It is demonstrated that innovative materials can exhibit sub-ambient surface temperatures and contribute highly to mitigate urban overheating. Highlights: New innovative mitigation materials are recently developed. Innovative advanced materials present a superior performance. New materials contribute to counterbalance urban overheating. Super cool materials operate under sub ambient surface temperatures.